2017
DOI: 10.1111/are.13485
|View full text |Cite
|
Sign up to set email alerts
|

Genetic identification of a newly synthetic allopolyploid strain with 206 chromosomes in polyploid gibel carp

Abstract: A newly synthetic allopolyploid strain (SAS) was selected and established from gynogenetic offspring of gibel carp clone A + with 156 chromosomes induced by common carp sperm with 50 chromosomes. In this study, the allopolyploid strain was detected to contain 206 chromosomes, and the growth trait was evaluated to have 25.15% growth faster than that of clone A + . Genetic marker analyses of transferrin (Tf) alleles, ITS1 sequences and mtDNA D-loop sequences indicated that the allopolyploid strain was synthetize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…On the other hand, although the dominant phyla in BL and BH group were Proteobacteria, Firmicutes and Cyanobacteria, while their relative abundance of the dominant phyla was significant difference, which indicated that the same fish (Beluga sturgeon) fed different diets were able to affect the intestinal microbiota. Lv et al [23] found that the relative abundances of intestinal microbiota were difference between the wild Kaluga ( Huso dauricus ) and cultured Kaluga sturgeon, and their predominant bacteria are Proteobacteria and Fusobacteria, respectively. Besides, there were reported that the microbiota composition of Atlantic Salmon ( Salmo salar ) was influenced by experimental diets when they fed with fishmeal, soybean meal or fermented soybean meal diets [30].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, although the dominant phyla in BL and BH group were Proteobacteria, Firmicutes and Cyanobacteria, while their relative abundance of the dominant phyla was significant difference, which indicated that the same fish (Beluga sturgeon) fed different diets were able to affect the intestinal microbiota. Lv et al [23] found that the relative abundances of intestinal microbiota were difference between the wild Kaluga ( Huso dauricus ) and cultured Kaluga sturgeon, and their predominant bacteria are Proteobacteria and Fusobacteria, respectively. Besides, there were reported that the microbiota composition of Atlantic Salmon ( Salmo salar ) was influenced by experimental diets when they fed with fishmeal, soybean meal or fermented soybean meal diets [30].…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture, colchicine treatment and chromosome preparation were the same as described (Liu, 2015). Two kinds of DNA probes were used to perform FISH analysis according to standard procedures as described previously (Lu et al, 2018). The fragments specific to sex chromosome B22 of C. auratus amplified by PCR (Tables S6 and S7 in Supporting Information) were labeled by DIG-Nick Translation Mix (Roche, Switzerland), and the green fluorescent signals were obtained with fluorescein isothiocyanate (FITC) conjugated-DIG antibody (Roche, Switzerland).…”
Section: Chromosome Preparation and Fluorescence In Situ Hybridization (Fish)mentioning
confidence: 99%
“…gibelio × C. carpio ( Gui et al. 1993a ; Lu et al. 2018 ), which might arise by the integration of C a .…”
Section: Discussionmentioning
confidence: 99%
“…1993a , 1993b ; Li et al. 2016 ; Lu et al. 2018 ), and some of them have been applied in aquaculture practice owning to their growth superiority ( Li et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation